(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2022)
Three hundred Iraqi people participated in demographic and attitudes study about red and white meat consumption. The mean age of the participants was 50 SD ± 11 years (mean 30-72); 51% were females and 49% males, mostly in forties who lived ≥ 5 years in Baghdad. The results showed that 80% of individuals prefer red meat. A 90% of people prefer fresh meat compared to frozen and processed meat. A 60% of people buy meat from popular markets. Nearly 87% of respondents believe the improving of livestock sector is essential and 80% of people confirmed there are obstacles to development this sector. An 80% of participates thought the reasons of the high prices of local fresh meat is the lack of planning and support to livestock sector. A survey also include chronic diseases assessment, a 60% of the individuals suffer from some chronic diseases, 23% of them suffer from cardiovascular diseases, 13% from diabetes, 21% had arthritis, and 3% were exposed to various types of benign or malignant tumors. In addition, the study appeared 30% of the sample suffered from gastrointestinal diseases such as diarrhea, colic, colitis, and acidity of the stomach and 21% were suffering from urinary problems. It has noticed that there is risk factor of urinary system diseases, arthritis and diabetes with excessive consumption of red meat. We recommend more attention to the local livestock sector and urging people to eat moderation of fresh and white meat, reduce red meat consumption.